2017
DOI: 10.23928/foldt.kozl.2017.147.3.225
|View full text |Cite
|
Sign up to set email alerts
|

A cirkon (U-Th)/He kormeghatározás módszertani alapjai és alkalmazása fiatal (<1 Ma) vulkánkitörések datálására

Abstract: The dating of young volcanic eruptions is often difficult with respect to the time range between the sensitivities of radiocarbon and the routine K-Ar methods (ca. 50 ka and 1 Ma, respectively); problems can also arise due to the absence of suitable K-bearing minerals (e.g. leucite, sanidine) or charcoal fragments. However, by combining zircon U-Th and (UTh)/He dating this critical time-window can be covered. Because of the low closure temperature of the zircon (U-Th)/He system (~150-180 °C), and the fact that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…During the last decade, several comprehensive review papers have been reported on the (U-Th)/He method in general (e.g., Farley, 2002), with a special focus on zircon (e.g., Reiners, 2005) and its Quaternary tephrochronological aspects (e.g., Farley et al, 2002;Schmitt et al, 2010a;Schmitt, 2011;Danišík et al, 2017;Molnár et al, 2017). Now, I will briefly summarize the theoretical basis of the (U-Th)/He geochronology concentrating only on the zircon for dating young volcanic events.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…During the last decade, several comprehensive review papers have been reported on the (U-Th)/He method in general (e.g., Farley, 2002), with a special focus on zircon (e.g., Reiners, 2005) and its Quaternary tephrochronological aspects (e.g., Farley et al, 2002;Schmitt et al, 2010a;Schmitt, 2011;Danišík et al, 2017;Molnár et al, 2017). Now, I will briefly summarize the theoretical basis of the (U-Th)/He geochronology concentrating only on the zircon for dating young volcanic events.…”
Section: Theoretical Backgroundmentioning
confidence: 99%